2006
DOI: 10.1128/aac.00521-06
|View full text |Cite
|
Sign up to set email alerts
|

Origins and Evolution of Methicillin-ResistantStaphylococcus aureusClonal Lineages

Abstract: Most methicillin-resistantRecently, some of these isolates were shown to have the same genetic backgrounds as contemporary epidemic MRSA isolates, and Danish methicillin-susceptible S. aureus (MSSA) isolates from the 1960s with a PST antibiotype were proposed to have been the recipients of the mecA gene in those lineages. In this study, we investigated the genetic backgrounds of isolates from the 83A complex that were fully susceptible or resistant to penicillin only in order to try to trace the evolutionary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
44
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 51 publications
6
44
0
5
Order By: Relevance
“…they cannot be distinguished by currently used typing procedures. Interestingly, according to MLST, most MRSA clones that frequently are associated with nosocomial infections today also were predominant among MSSA isolates recovered during the 1960s from hospitals in Denmark (14) and more recently in England (15) and Belgium (16). Similar results were obtained in a carriage study from the United States by DNA macrorestriction analysis (17).…”
supporting
confidence: 72%
“…they cannot be distinguished by currently used typing procedures. Interestingly, according to MLST, most MRSA clones that frequently are associated with nosocomial infections today also were predominant among MSSA isolates recovered during the 1960s from hospitals in Denmark (14) and more recently in England (15) and Belgium (16). Similar results were obtained in a carriage study from the United States by DNA macrorestriction analysis (17).…”
supporting
confidence: 72%
“…The whole genetic background contributes to epidemiological success. Only fi ve main MRSA clonal complexes, specifi ed by MLST, are present in hospitals around the world [19]. A retrospective study has shown that MSSA isolates from the 1960s belonged to the same clonal complexes as MRSA, suggesting that these genetic lineages, carrying genes contributing to superior epidemicity, were present in hospitals before the acquisition of SCCmec element [19].…”
Section: Discussionmentioning
confidence: 99%
“…Only fi ve main MRSA clonal complexes, specifi ed by MLST, are present in hospitals around the world [19]. A retrospective study has shown that MSSA isolates from the 1960s belonged to the same clonal complexes as MRSA, suggesting that these genetic lineages, carrying genes contributing to superior epidemicity, were present in hospitals before the acquisition of SCCmec element [19]. Similarly, successful clones circulating in the community are ST1 and ST8, mostly reported in the USA and Canada, ST80 in Europe, ST59 in the Asia-Pacifi c, Taiwan and Australia, and ST30 in the USA, Europe, western Pacifi c, Japan, and other countries worldwide [4].…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported by other authors (7, 10, 52), a higher diversity of CCs was found among the MSSA isolates of the HUCA, which accounted for 67.9% of the analyzed isolates. Of them, 80.0% had a genetic background common to major MRSA lineages, namely, CC5 (38.2%), CC30 (25.5%), CC45 (14.5%), and CC8 (1.8%) (7,17,48). As was the case for MRSA, MSSA isolates with a CC5 genetic background mostly belonged to SmaI PFGE subclusters G1 and G2 and were of either ST5 or ST125; CC30 isolates fell into SmaI PFGE cluster B and were of ST30; and ST47 and ST45, both members of CC45, were separated by SmaI PFGE into clusters A and D. Four successful MSSA lineages different from the major MRSA clones, namely, CC12, CC15 (PFGE clusters F and E), CC51, and CC59 (each with one sporadic isolate), were also detected.…”
Section: Discussionmentioning
confidence: 99%